2016
DOI: 10.1111/apm.12599
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin‐like kinase 1‐positive enterocyte – a new cell type in human intestine

Abstract: Doublecortin-like kinase 1 (DCLK1) is a microtubule-associated kinase. In murine intestine, DCLK1 marks tuft cells with characteristic microvilli, features of neuroendocrine cells and also quiescent stem cell-like properties. The occurrence and pathological role of DCLK1-positive cells in human intestinal mucosa is unknown. We analysed DCLK1 expression in healthy duodenal, jejunal and colorectal mucosa samples (n = 35), and in duodenal specimens from patients with coeliac disease (n = 20). The samples were imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…The serine/threonine-protein kinase, doublecortin-like kinase 1 (Dclk1), is an established tuft cell marker in the mouse alimentary tract 7,44 , but recently was described to be restricted to a subset of enteroendocrine cells in the human intestine 45 . Using the same antiserum, we could confirm that DCLK1 is expressed by ChAT-ir tuft cells in the mouse gastro-intestinal system (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The serine/threonine-protein kinase, doublecortin-like kinase 1 (Dclk1), is an established tuft cell marker in the mouse alimentary tract 7,44 , but recently was described to be restricted to a subset of enteroendocrine cells in the human intestine 45 . Using the same antiserum, we could confirm that DCLK1 is expressed by ChAT-ir tuft cells in the mouse gastro-intestinal system (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that TRPM5 plays an important role in regulating the intestinal inflammatory response and epithelial integrity. Another study showed that the number of DCLK1-positive cells decreased in intestinal tissue from patients with celiac disease [ 45 ]. Meanwhile, our study found no alteration in TRPM5 expression in PBMCs from either UC or CD patients, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They did not show morphological features typical to tuft cells, as reported in animal studies, 1,2 but instead showed an apical brush border of even thickness. 3 In the duodenum, they found colocalization of synaptophysin and DCLK1, suggesting a neuroendocrine role for these cells in this region.…”
Section: Introductionmentioning
confidence: 92%
“…1,2 A recent paper by Leppänen et al documented the expression of DCLK1-positive enterocytes in the human intestine for the first time. 3 Tuft cells were found along the entire length of the human gastrointestinal (GI) tract. These cells were seen to be scattered between the crypts and villi, with DCLK1 expressed on the basal pole of each cell.…”
Section: Introductionmentioning
confidence: 99%